Improved Teaching and Learning Process in the Mechanical Engineering Career. Micro-Curricular Redesign Based on Learning Outcomes [Mejora del Proceso de Enseñanza y Aprendizaje en la Carrera de Ingeniería de Ejecución Mecánica. Diseño Micro-Curricular Basado en Resultados de Aprendizaje] - Avagliano-Gaeta, A; Vega-Yanez, S (2013)
This work corresponds to a quasi-experimental research focused on micro-curricular design in the context of improving the teaching-learning process in two subjects of the mechanical engineering career of the Universidad de Santiago de Chile. For the study, an Interactive Digital Classroom was acquired and implemented and an experimental group and a control group in the course of Projects Formulation and a qualitative case study to the subject of Thermal Systems were considered. In both courses the curricular programs based on learning outcomes, graduate profile and institutional educational model were designed. The results show that academic performance improved by 20% in the experimental group compared to the control group that used the current curricular design. This will allow modifying teaching strategies and achieving greater academic equity between different personal ways of learning.